The art of paper cutting - Melichson, Henya (Quarry Books, 2011)
Papercutting is an ancient, elegant art that dates almost as far back as the creation of paper itself. In today's multicultural world, papercutting embraces any number of themes, designs, and images. It is an all-inclusive art that requires few tools and minimal materials. All one needs is instruction and inspiration, both of which are found in good measure in The Art of Papercutting . The book includes more than 20 projects that feature a range of sizes, subject matters, and techniques. Every project features step-by-step photographs and numerous helpful hints.
Keywords: Paper work; Handicraft; Travail du papier; Artisanat; crafts (art genres)